1994
DOI: 10.1002/pola.1994.080321606
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the particle growth mechanism in propylene polymerization with MgCl2‐supported ziegler–natta catalysts

Abstract: To elucidate the particle growth mechanism in propylene polymerization with high‐yield MgCl2‐supported Ziegler‐Natta catalysts, observations have been carried out by electron microscopy on a series of samples having different degrees of polymer growth (from 0.1 to 1000 g/g of catalyst). Topics such as surface and bulk morphology, catalyst fragmentation, as well as distribution of the catalyst residues in the polymer have been investigated. The experimental data suggest that if the site distribution in the cata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(59 citation statements)
references
References 22 publications
2
57
0
Order By: Relevance
“…[5][6][7][8][9][10][11][16][17][18][19][20][21][22][23][24][25][26][27] Two catalyst fragmentation behaviors are reported in these studies. Ferrero, Chiovetta and Fink [18][19][20][21][22][23][24][25][26] used electron microscopy technique to investigate the key parameters that affect the catalyst fragmentation in MgCl 2 supported Ziegler-Natta catalysts and silica supported metallocene catalysts.…”
Section: Different Fragmentation Behaviormentioning
confidence: 97%
“…[5][6][7][8][9][10][11][16][17][18][19][20][21][22][23][24][25][26][27] Two catalyst fragmentation behaviors are reported in these studies. Ferrero, Chiovetta and Fink [18][19][20][21][22][23][24][25][26] used electron microscopy technique to investigate the key parameters that affect the catalyst fragmentation in MgCl 2 supported Ziegler-Natta catalysts and silica supported metallocene catalysts.…”
Section: Different Fragmentation Behaviormentioning
confidence: 97%
“…New processes for the synthesis gies: the catalyst/polymer replication phenomeof new olefinic and nonolefinic polymers and non. In our company, detailed studies began in alloys have been developed [6][7][8] by exploiting this [1968][1969][1970] 2 and are still in progress [3][4][5] ; they concept, named the Reactor Granule Technology. pointed out that the replication of catalyst morRecently, new catalysts (i.e., the metallocenes) phology by olefin polymerization is allowed when have been proven useful for olefin polymerization: they allow the synthesis of homo-and copolymers larity, and narrow chemical composition distribu-(r-EBTHI) was prepared according to the method described in ref.…”
Section: Introductionmentioning
confidence: 99%
“…22,24 The polymerization started everywhere in the particle more or less simultaneously, typical for MgCl 2 -based ZN PP catalyst. [25][26][27][28] The fragmentation model best describing how this catalyst break up in the early stage of polymerization is the continuous bisection fragmentation model. 29,30 It has also been shown that the MgCl 2 nano-ribbons at a very early stage in polymerization break up into the primary catalyst particles.…”
Section: Internal Morphology Of Hipp Particles Produced Withmentioning
confidence: 99%